Influence of noncircular chainring on male physiological parameters in hand cycling - Zeller, S.; Abel, T.; Smith, P. M.; Strueder, H. K. (Journal of Rehabilitation Research & Development, 2015)
The purpose of this study was to examine the influence of a noncircular chainring (NCC) compared with a con ventional circular chainring (CC) on hand cycling performance. Eleven nondisabled male participants with no hand cycling experience initially completed an incremental exercise test. Afterward, the participants completed two 20 s sprint tests, fol lowed by a 20 min endurance test and then another two 20 s sprint tests. An NCC and a CC were used in random order on two separate occasions. To compare the effects of the NCC and CC on power data of the sprint tests and metabolic response during the endurance test, a two-way analysis of variance for repeated measures was used. Average power values of the sprint tests showed no significant difference between NCC and CC, but over time, values of the first and third sprint tests were higher than those of the second and fourth sprint tests for both chainrings. Values of energy expenditure (kilojoules), gross efficiency (percentage), and net efficiency (percentage) after 10 and 20 min during the endurance test using NCC and CC showed no significant differences (p > 0.05) either between tests or over time. Under the current test conditions and focus ing on physiological parameters, a performance optimization using an NCC in hand cycling could not be proven.